(untitled) (EU and comparative law issues and challenges series (ECLIC), 2019)
The paper analyses recent decisions delivered by the Court of Justice of the European Union (CJEU) addressing the contemporary challenges facing selective distribution systems. It addresses the legality of restrictions of online sales imposed on distributors. In Coty, a case concerning the selective distribution of luxury products, the CJEU ruled that the restriction of using third-party platforms was compatible with competition law. In order to reach that conclusion, it relied on its trademark jurisprudence. In this regard, several issues emerge: the link between trademark and competition law and the applicability of the ruling on non-luxury products. Coty presents a departure from the CJEU’s earlier judgement delivered in Pierre Fabre and different national authorities interpreted it differently. It seems that the debate over these issues is far from over. The purpose of this paper is to contribute to the discussion trying to reconcile diverging decisions. It is principally based on a case-law analysis, providing critical assessment of the decisions under scrutiny (i.e. CJEU’s case law and the divergent decisions delivered by different national authorities). The study is supported by an analysis of scientific legal and economic papers concerning selective distribution and e-commerce. The research shows that the outcome of the cases depends largely on the concrete factual circumstances. However, certain points appear to be relevant for all the analysed cases, i.e. the applicability of Coty to non-luxury products and the extent of restrictions that triggers the breach of competition law.